Health professional educators’ experiences of interprofessional socialisation within higher education: An interpretative phenomenological study - Stanley, Karen Christine (Curtin University, 2016)
This interpretative phenomenological study explored health professional educators’ understanding and experiences of inter-professional socialisation within higher education in Perth, WA. The analysis of one-to-one interviews comprised of 26 HPEs’ from various health related disciplines across 5 universities within WA. Qualitative content analysis led to the development of five themes. A newly developed Health Educators Inter-Professional Socialisation framework is proposed along with socialisation strategies that could positively influence IP collaboration between educators within higher education.